2019
DOI: 10.24325/issn.2446-5763.v5i14p189-205
|View full text |Cite
|
Sign up to set email alerts
|

Percepção Da Arborização Urbana Por Estudantes De Marketing

Abstract: A arborização urbana exerce influência direta em nossas vidas, sobretudo num país tropical como o Brasil, no tocante ao microclima. Entretanto, diverge opiniões quanto à sua aceitação. O objetivo foi verificar a percepção de estudantes de marketing quanto à arborização urbana, para que os tomadores de decisão possam verificar o nível de conscientização ambiental e a percepção do marketing quanto às árvores, obtendo, assim, informações importantes para o planejamento urbano. Por meio de um questionário on-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
0
0
3
Order By: Relevance
“…Limited education and communication are already known crucial barriers to the scale-up of NBS and are acknowledged as important enablers of NBS uptake (Pauleit et al 2017, Davies and Lafortezza 2019, Sarabi et al 2019. In line with findings from urban NBS studies in other countries (Mendes and Oliveira 2019, Dorst et al 2022, Vojvodíková et al 2022, the results of this study identified the NIMBY phenomenon as a barrier for NBS integration and planning, despite commonly occurring in large infrastructure projects. This highlights the importance of creating synergies with municipal education and communication departments for enhancement of public awareness and NBS acceptance.…”
Section: Horizontal Integrationsupporting
confidence: 86%
“…Limited education and communication are already known crucial barriers to the scale-up of NBS and are acknowledged as important enablers of NBS uptake (Pauleit et al 2017, Davies and Lafortezza 2019, Sarabi et al 2019. In line with findings from urban NBS studies in other countries (Mendes and Oliveira 2019, Dorst et al 2022, Vojvodíková et al 2022, the results of this study identified the NIMBY phenomenon as a barrier for NBS integration and planning, despite commonly occurring in large infrastructure projects. This highlights the importance of creating synergies with municipal education and communication departments for enhancement of public awareness and NBS acceptance.…”
Section: Horizontal Integrationsupporting
confidence: 86%
“…Devido a exuberância de suas flores, os ipês são apontados, majoritariamente, para fins ornamentais, considerando suas cores vibrantes que destoam com a paisagem verdejante da natureza e de áreas urbanas Oliveira, 2019). Além disso, o ipê também é considerado a árvore símbolo do país (Marques et al, 2022).…”
Section: • Ipêsunclassified
“…Os povos originários utilizavam a madeira do ipê, com a finalidade de preparar arcos de caça para se defenderem, em razão disso é conhecido como pau d´arco (IBF, 2022). Devido a exuberância de suas flores, os ipês são apontados, majoritariamente, para fins ornamentais, considerando suas cores vibrantes que destoam com a paisagem verdejante da natureza e de áreas urbanas (Mendes;Oliveira, 2019). Além disso, o ipê também é considerado a árvore símbolo do país (Marques et al, 2022).…”
Section: • Ipêsunclassified